Water Wars: A "Critical Listening In" to Rural Radio Discourse on a River System in Trouble. Issue 3 (3rd April 2021) - Mesikämmen, Emma; Waller, Lisa; Burkett, Brian
ABSTRACT: For news media on the earth's driest continent, changes in the health and politics of Australia's largest river system, the Murray-Darling, have been a major national focus for decades. In recent times, climate crisis, drought and policy failure have combined to threaten its future, putting the issue under intense public scrutiny. This article offers a critical discourse analysis of specialist rural radio coverage of the issue in 2018–19. It identifies the discourses that the Country Hour program presents and considers the voices and viewpoints that are absent. Two critical discourse moments are analyzed: an ecological disaster in which more than one million fish died, and #watergate – a pre-election scandal over commercial water rights. We map the strategies and roles of Country Hour journalists and other social actors in legitimating the "productive use" of the river system above all else, politicizing the issue and shifting responsibility for the river's wellbeing.